Allelic status of key genes of carotenogenesis on DNA-markers in maize lines and their hybrids - Ю. О. Гончаров; Т. М. Сатарова; Б. В. Дзюбецький; В. Ю. Черчель (Plant Varieties Studying and Protection)
Purpose. The analysis of allelic status of such key genes of carotenogenesis as gene of lycopene-ε-cyclase (lcyε) and gene of β-carotene hydroxylase (crtRB1) for DNA-markers in domestic maize lines and their hybrids. Methods. DNA isolation, PCR, gel electrophoresis. Results. Allelic status of key genes of carotenogenesis was investigated in eight maize inbred lines and their single crosses. Molecular genetic polymorphism in the studied sample of maize lines and hybrids has been detected in gene of β-carotene hydroxylase for marker crtRB1-3’TE. For this gene, codominant character of inheritance of alleles of parental lines in single crosses was confirmed. For markers of gene of lycopene-ε-cyclase lcyε-3’INDL and lcyε-SNP216, polymorphism in the group of investigated lines and hybrids has not been identified, genotypes included only one variant of alleles for each marker. For lines ‘DK253ZSZM’, ‘DK633/266zS,zM’, ‘DK366zS,zM’ and hybrids ‘DK296S×DK253ZSZM’, ‘DK272S×DK633/266zS,zM’ and ‘DK231S×DK366zS,zM’, the decrease of the activity of β-carotene hydroxylase owing to the mutation of gene crtRB1 under the influence of transposone element at the 3’-end, the inhibition of β-carotene transition into β-cryptoxanthin can be expected, that allows to predict β-carotene accumulation in grain. Conclusions. The study of allelic status of carotenegenesis gene of lycopene-ε-cyclase in maize showed no polymorphism for markers lcyε-3’INDL and lcyε-SNP216 in eight inbred lines and their single crosses, along with this, for marker lcyε-3’INDL in genomes of all studied samples the allele was identified to be favorable for the accumulation of β-carotene. For marker crtRB1-3’TE of gene of β-carotene hydroxylase, the studied breeding material was polymorphic. Allele of crtRB1 being favorable for the accumulation of β-carotene was identified in lines ‘DK253ZSZM’, ‘DK633/266zS,zM’, ‘DK366zS,zM’ and hybrids ‘DK296S×DK253ZSZM’, ‘DK272S×DK633/266zS,zM’ and ‘DK231S×DK366zS,zM’. Single crosses inherit maternal and paternal alleles of gene of β-carotene hydroxylase codominantly.